NILAI KEMANUSIAAN DALAM ESAI FOTO JURNALISTIK “MEREKA MASIH BUTUH BANTUAN” PADA RUBRIK ESFOS SURAT KABAR HARIAN FAJAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study is entitled "The Value of Humanity in Journalistic Photo Essays" They Still Need Help "in the ESFOS Rubric of the FAJAR Daily Newspaper". The purpose of this study is to analyze the meaning of denotation, connotation, and myth in images and to find out the representation of human values in a photo essay published after the five-month disaster in Palu City and its surroundings. The theory used is Roland Barthes's semiotic analysis which learns about codes as signs or something that has meaning. The meaning of denotation is obtained the eight photos that the photographer wants to show to the reader about the condition of the location and victims of disasters in Palu City and its surroundings. To connotation, meaning explains the meaning behind pictures, and all photos do not exist through manipulation that makes the situation different from reality, and for the definition of myth is defined by the trust that develops in society. Lastly, the representation of human values in this study contained several points that researchers found, such as high solidarity, togetherness, sympathy and empathy, the sincerity of the feeling of being aroused by trials and motivation to continue living.